Emerging Treatment Options for Myelofibrosis: Focus on Anemia - Sastow D; Tremblay D (Dove Medical Press, 2023)
Dahniel Sastow,1 Douglas Tremblay2 1Department of Internal Medicine, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Tisch Cancer Institute, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Douglas Tremblay, Tisch Cancer Institute, Division of Hematology/Oncology, Icahn School of Medicine at Mount Sinai, 1 Gustave L Levy Place, Box 1079, New York, NY, 10029, USA, Email Douglas.tremblay@mssm.eduAbstract: Myelofibrosis (MF) is a hematologic malignancy characterized by abnormal proliferation of myeloid cells and the release of pro-inflammatory cytokines, leading to progressive bone marrow dysfunction. The introduction of ruxolitinib just over a decade ago marked a significant advancement in MF therapy, with JAK inhibitors now being the first-line treatment for reducing spleen size and managing symptoms. However, early JAK inhibitors (ruxolitinib and fedratinib) are often associated with cytopenias, particularly thrombocytopenia and anemia, which limit their tolerability. To address these complications, pacritinib has been developed and recently approved for patients with thrombocytopenia, while momelotinib is in development for those with anemia. Although JAK inhibitors have significantly improved the quality of life of MF patients, they have not demonstrated the ability to reduce leukemic transformation and their impact on survival is debated. Numerous drugs are currently being developed and investigated in clinical trials, both as standalone therapy and in combination with JAK inhibitors, with promising results enhancing the benefits of JAK inhibitors. In the near future, MF treatment strategies will involve selecting the most suitable JAK inhibitor based on individual patient characteristics and prior therapy. Ongoing and future clinical trials are crucial for advancing the field and expanding therapeutic options for MF patients.Keywords: myelofibrosis, emerging therapy, momelotinib, anemia, JAK inhibitors